Reliability and patentability of academic-rank promotional criteria in medical colleges of India - sorte, Smita Rameshrao; Rathod, Sachin Babu (Journal of Bangladesh Society of Physiologist, 2018)
A promotion refers to the progress of an employee’s position or ranks in a hierarchical constitution with an increase in status, responsibilities, and salary. Academic rank Promotional criteria considered by the Medical Council of India (MCI) include educational qualifications, seniority according to years of teaching experience and numbers of Publications. There is gap between faculty role in medical college and expectation for promotion in India. Impractical expectation beyond the self-competency has promoted unethical practices. The various scientific misconduct problems had faded the quality of research in India. So the expected criteria for the evaluation of faculty members are needed to be re-adjusted by policymakers, according to the facilities of the scientific centers and human, social and economic resources at the institute. Medical Council of India needs to evolve and implement a suitable promotional policy for faculty members of medical colleges in India. J Bangladesh Soc Physiol. 2018, December; 13(2): 78-83